Analisis Potensi Pengembangan Ekowisata Pantai Pondok Bali Desa Mayangan, Kecamatan Legonkulon, Kabupaten Subang - Lindiyani Lindiyani; Tri Cahyanto (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
Pondok Bali Beach, which is located in a coastal area rich in natural and cultural beauty, has great potential for ecotourism development. This research aims to analyze the potential for ecotourism at Pondok Beach in Bali and identify sustainable development strategies. The methods used include field surveys, interviews with local communities, visitors and managers, as well as SWOT to understand the strengths, weaknesses, opportunities and threats in ecotourism development. The parameters measured in data collection are attractions, amenities, accessibility and community involvement. The analysis results show that Pondok Bali Beach has a great opportunity to be developed as an ecotourism destination. By considering the existing attractions, as well as adequate accessibility factors, amenities and attractions, coupled with the active participation of the local community, this potential can be maximized